Context and Content in the Interpretation of Isaiah 7:14 - Motyer, J. A. (Tyndale bulletin, 1970)
The Immanuel prophecy cannot be confined to any long-forgotten ‘fulfilment’ in Ahaz’s time; the biblical claim of its fulfilment in Jesus is not only justified, but illuminates Isaiah's forecast.